2021
DOI: 10.1371/journal.pgen.1009467
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of origins to load MCM establishes replication timing patterns

Abstract: Loading of the MCM replicative helicase at origins of replication is a highly regulated process that precedes DNA replication in all eukaryotes. The stoichiometry of MCM loaded at origins has been proposed to be a key determinant of when those origins initiate replication during S phase. Nevertheless, the genome-wide regulation of MCM loading stoichiometry and its direct effect on replication timing remain unclear. In order to investigate why some origins load more MCM than others, we perturbed MCM levels in b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 64 publications
(138 reference statements)
2
20
2
Order By: Relevance
“…In addition, this study revealed that more MCMs were loaded at early rather than late origins, thus increasing the probability that these origins fire early in the S-phase. Very recently, the same laboratory demonstrated that a reduction in the global cellular pool of MCMs causes significant delays in RT [ 138 ]. This strongly suggests that the expression level of MCMs is an important factor in the regulation of the RT program.…”
Section: Causes Of Replication Timing Changes In Cancersmentioning
confidence: 99%
“…In addition, this study revealed that more MCMs were loaded at early rather than late origins, thus increasing the probability that these origins fire early in the S-phase. Very recently, the same laboratory demonstrated that a reduction in the global cellular pool of MCMs causes significant delays in RT [ 138 ]. This strongly suggests that the expression level of MCMs is an important factor in the regulation of the RT program.…”
Section: Causes Of Replication Timing Changes In Cancersmentioning
confidence: 99%
“…In many species, replication timing in S phase shows a general (though not exclusive) pattern of early euchromatin replication and late heterochromatin replication 71, 72 . Differences in the density of G1 MCM loading at different individual loci have been implicated in these S phase replication timing differences; more ORC or MCM loading in G1 correlates with early firing origins 17, 60, 73 . Early firing in S and early G1 origin licensing may both be consequences of general DNA accessibility in euchromatin.…”
Section: Discussionmentioning
confidence: 99%
“…The relative amounts of loaded MCM complexes and MCM loading factors, particularly the Origin Recognition Complex, have been implicated in establishing replication timing programs within S phase. Furthermore, some links between MCM loading efficiency and chromatin features or chromatin modifying enzymes are known [16][17][18][19] . The Sir2 histone deacetylase is required for normal MCM distribution among budding yeast origins 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Each replication origin in the genome has an inherent efficiency which is thought to be determined, at least in part, by ORC binding, Mcm2-7 loading, the recruitment of activation factors, and the local chromatin environment [2,20,26,27,36,37]. We had previously used genome-wide chromatin occupancy profiling to identify ORC-dependent small fragment occupancy footprints at replication origins in two discrete phases of the cell cycle --G1 and G2 [20].…”
Section: Cell Cycle-dependent Changes In Replication Initiation Factor Occupancy At Replication Originsmentioning
confidence: 99%
“…In addition, the inherent initiation efficiency [2] and the time of activation [3,24] of each origin are also thought to be regulated, in part, by the local chromatin environment and the levels of chromatin associated ORC [20,25] and Mcm2-7 [26,27].…”
Section: Introductionmentioning
confidence: 99%